2016
DOI: 10.1007/s11432-016-0278-5
|View full text |Cite
|
Sign up to set email alerts
|

An overview of transmission theory and techniques of large-scale antenna systems for 5G wireless communications

Abstract: To meet the future demand for huge traffic volume of wireless data service, the research on the fifth generation (5G) mobile communication systems has been undertaken in recent years. It is expected that the spectral and energy efficiencies in 5G mobile communication systems should be ten-fold higher than the ones in the fourth generation (4G) mobile communication systems. Therefore, it is important to further exploit the potential of spatial multiplexing of multiple antennas. In the last twenty years, multipl… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
31
0
4

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
3
1

Relationship

5
5

Authors

Journals

citations
Cited by 87 publications
(35 citation statements)
references
References 76 publications
(71 reference statements)
0
31
0
4
Order By: Relevance
“…The use of massive antennas was first proposed for multicell multi-user cellular systems in [1] and since then, it has received much research interest [2]- [5]. It was shown that massive multi-input multi-output (MIMO) has very large performance gains compared with the conventional MIMO provided that a sufficiently large number of transmit antennas per active user are employed at each base station (BS).…”
Section: Introductionmentioning
confidence: 99%
“…The use of massive antennas was first proposed for multicell multi-user cellular systems in [1] and since then, it has received much research interest [2]- [5]. It was shown that massive multi-input multi-output (MIMO) has very large performance gains compared with the conventional MIMO provided that a sufficiently large number of transmit antennas per active user are employed at each base station (BS).…”
Section: Introductionmentioning
confidence: 99%
“…For 5G NR scenarios, these problems are more challenging due to the complicated network structures and large number of KPIs. Applications of new features like massive MIMO beamforming [25] are associated with high-dimensional optimization parameters and the optimization problem itself is difficult to model. Also, 5G NR involves multiple KPIs including peak data rate, spectral efficiency, latency, connection density, quality of experience (QoE) and so on.…”
Section: Research Directions For Ai In 5gmentioning
confidence: 99%
“…MIMO has become a key technology of many wireless communications standards. By using large-scale antenna arrays at the base station, which is also known as massive MIMO, performance could be further improved [7]- [9]. Massive MIMO has been adopted by the 5G NR standard.…”
Section: Introductionmentioning
confidence: 99%